2022
DOI: 10.1111/csp2.12684
|View full text |Cite
|
Sign up to set email alerts
|

Multiple anthropogenic pressures challenge the effectiveness of protected areas in western Tanzania

Abstract: Despite being key conservation instruments, the ecological effectiveness of protected areas (PAs) is contested. To assess the ecological effectiveness of PAs in the Katavi-Rukwa Ecosystem (KRE) in western Tanzania, we investigated temporal changes in land-use and population densities of six large mammal target species (elephant, buffalo, giraffe, zebra, topi, and hartebeest) across

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(32 citation statements)
references
References 92 publications
1
24
3
Order By: Relevance
“…There are several factors related to the diversity of human activities occurring outside the park boundaries which may contribute to the observed spatial distribution of both zebra and wildebeest in relation to hard versus soft boundaries of the Serengeti National Park. These include the rate of land‐use conversion to agriculture, the effects of human disturbance, livestock incursions into the protected area and bushmeat hunting, as observed in similar ecosystems (Giliba et al., 2022). The extent of these activities is largely determined by national policies that permit certain activities in specific areas (such as trophy hunting in game reserves) and by village land‐use policies in the areas beyond the protected areas which focus on subsistence agriculture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several factors related to the diversity of human activities occurring outside the park boundaries which may contribute to the observed spatial distribution of both zebra and wildebeest in relation to hard versus soft boundaries of the Serengeti National Park. These include the rate of land‐use conversion to agriculture, the effects of human disturbance, livestock incursions into the protected area and bushmeat hunting, as observed in similar ecosystems (Giliba et al., 2022). The extent of these activities is largely determined by national policies that permit certain activities in specific areas (such as trophy hunting in game reserves) and by village land‐use policies in the areas beyond the protected areas which focus on subsistence agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…Protected areas are often designed to reduce habit loss as well as stem biodiversity loss across the world (Pimm et al., 2001). Despite their important role in biodiversity conservation, achieving the desired goal is difficult due to incompatible land use regimes on the adjacent landscapes (Castro‐Prieto et al., 2017; Giliba et al., 2022; Joppa et al., 2009). It is possible that the associated land‐use conversion may account for the patterns we observe in the abundance of wild animals inside the protected area.…”
Section: Discussionmentioning
confidence: 99%
“…A robust and updated assessment of the ecological outcomes of PAs is particularly important for the Katavi‐Rukwa Ecosystem of western Tanzania. Partially fuelled by immigration, this ecosystem has experienced substantial human population growth (Salerno et al, 2017); associated changes in land use (Giliba et al, 2022) and high rates of illegal wildlife hunting observed in this ecosystem (Martin & Caro, 2013) have been hypothesised to contribute to rapid wildlife population declines (Caro et al, 2013). Based on aerial survey data, several authors have observed ecosystem‐wide declines in large herbivore species (Caro et al, 2013; Giliba et al, 2022; Mtui et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Partially fuelled by immigration, this ecosystem has experienced substantial human population growth (Salerno et al, 2017); associated changes in land use (Giliba et al, 2022) and high rates of illegal wildlife hunting observed in this ecosystem (Martin & Caro, 2013) have been hypothesised to contribute to rapid wildlife population declines (Caro et al, 2013). Based on aerial survey data, several authors have observed ecosystem‐wide declines in large herbivore species (Caro et al, 2013; Giliba et al, 2022; Mtui et al, 2017). Over a span of 27–37 years, aerial survey data revealed a non‐significant negative trend in the elephant ( Loxodonta africana ) population and significant declines in populations of giraffe ( Giraffa camelopardalis tippelskirchi ), buffalo ( Syncerus caffer ), zebra ( Equus quagga ), topi ( Damaliscus lunatus ), and hartebeest ( Alcelaphus buselaphus ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation